Establishing an Optical Measuring Method to Determine the Anisotropy of Embroidered Reinforcement Structures. (3rd January 2019) - Breier, A.; Guan, J.; Spickenheuer, A.
ABSTRACT: BioEmbroidery for medical applications offers the potential of a directed fiber alignment, density and distribution and allows the production of properties that are customized to the needs. The adaption of the mechanical properties of biomaterials to the requirements of human tissues often results in substrates with space-resolved distribution of stress and thus highly anisotropic behavior. A demonstrative example for such a material would be a stress adapted hernia mesh showing a high stiffness in the area of the abdominal opening and a graduated transition in the marginal area discharging into the material properties of the surrounding tissue. For evaluating the influence of the reinforcement patterns a measuring method had to be established featured by the optical measuring system ARAMIS. This study was drafted to establish a method to analyze embroidered reinforcement structures by optical measurement. A feasible base material had to be identified showing a high and isotropic elasticity assuring no influence on the measuring outcomes. A proper procedure had to be established to gain suitable data and to define significant criterions. An embroidered reinforcement pattern could be applied on an isotropic polyurethane foil (Ellastolan soft 45, BASF Polyurethanes, Germany) and tested in a biaxial texting device successfully in uni- and equibiaxial direction. The images could be edited with ARAMIS software, the deformation visualized and local strains determined. An optimum tuning for the ARAMIS parameters facet size and grid point distance could be identified. By placing section lines parallel to the x- and y- axis during deformation a medium strain could be calculated, allowing the quantification of an anisotropy criterion. A higher anisotropy of the reinforced embroidered samples compared to the plain foils could be proved. The measuring set-up established a method to evaluate the influence of different embroidered reinforcement patterns on the anisotropy of the base material.